Incomati Basin-wide model workshop: Engaging with results, planning for handover - Fakudze, Buyani; Lautze, Jonathan F. (CGIAR, 2024)
A workshop organized by IWMI and the Incomati and Maputo Watercourse Commission brought together a community of practice to share progress made using the Incomati Basin-wide model